The Impact of Electronic Medical Records on BPJS Claims and Physician Performance - Sharah Aulia Winarsih; Bagoes Widjanarko; Farid Agushybana (Jurnal Indonesia Sosial Teknologi, 2024)
With the digital transformation, Electronic Medical Records (EMR) have become crucial for operational efficiency and better healthcare. By the end of 2023, all Indonesian healthcare facilities are expected to implement EMR (Regulation No. 24, 2022). However, challenges with BPJS claims often arise post-EMR implementation. This study analyzes EMR's impact at RS A on BPJS claims and physician performance, aiming to identify mitigation strategies for these issues. Using mixed methods, this study combines primary data from 5 respondent interviews and secondary data on BPJS claims pre- and post-EMR implementation at RS A (Jan-Aug 2023). Secondary data analysis employs tables, graphs, and descriptive statistics (mean, median, and standard deviation) to detail BPJS claims patterns. The Chi-Square test is used to analyze the relationship between physician performance and BPJS claim document completeness. EMR implementation increased cases by 11.27% and nominal BPJS claims by 15.04%. Physician performance analysis showed no significant relationship between variables and BPJS claim document completeness (p > 0.05). Challenges post-EMR included data errors, lack of staff training, technical constraints, and incomplete integration of operational processes with EMR. Mitigation strategies include staff training, periodic monitoring, internal audits, process improvements, and management evaluation. EMR implementation at RS A increased cases and BPJS claims. However, challenges persist post-implementation. Effective mitigation strategies can enhance efficiency and BPJS claim quality.